Dynamic efficiency and inefficiency in a class of overlapping-generations economies with multiple assets - Martin Hellwig (Max Planck Institute for Research on Collective Goods, 2024)
For overlapping-generations models with multiple assets and without labour, welfare assessments of equilibrium allocations depend on whether the certainty equivalents of the one-period-ahead marginal rates of return on assets that are held are larger or smaller than the population growth rate. Conditional on the period and the history up to that period, the equilibrium values of these certainty equivalents are the same for all assets held and equal to the riskless rate if a riskless asset is held. If population growth is uncertain, the standard of comparison is the certainty equivalent of the population growth rate when interpreted as the marginal rate of return on an additional asset.
hdl:21.11116/0000-000E-721C-3
Keywords: D15; D61; E21; E22; E62; H30; 330; Dynamic Inefficiency; overlapping-generations models; First Welfare Theorem; certainty-equivalents criterion